THE ANALYSIS OF ACADEMIC INFORMATION SYSTEM IN DIRGANTARA MARSEKAL SURYADHARMA UNIVERSITY USING ISO/IEC 25010 - Anugrah Septianto; Kemal Ade Sekarwati (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2019)
Dirgantara Marsekal Suryadarma University (Unsurya) needs to improve the information system for the students. So that it needs to do a software quality test in SIAKAD and to ensure the feature and the function run well. It has a goal to know the quality of a software by testing from functional suitability, performance efficiency, compatibility, security and maintainability standardized by ISO/IEC 25010. It is done to improve the quality of academic information system to be better. This research analyzed the software quality insurance of academic information system in Unsurya by testing the aspects from main menu such as transcript, study plan, lecturer’s evaluation of learning activity, the print out of exam card, the consultation of academic supervisor, consultation from Head of Study Program and student’s financial. Based on the suitability functional and efficiency performance testing using black box in Unsurya SIAKAD system, it runs well although some functions don’t work well. The result for compatibility in SIAKAD Unsurya, it works in line with the browser in the desktop or mobile.  Based on the security test using audit system, it results the value 90 (B) with 1 medium risk and 9 low risk.   Based on the maintainability test, it results SIAKAD which is able to give a system needed by the students.